2018
DOI: 10.1177/0264550518790677
|View full text |Cite
|
Sign up to set email alerts
|

The bridge between social identity and community capital on the path to recovery and desistance

Abstract: It has long been recognised that changes in social networks (and the underpinning changes in personal and social identity) are strong predictors of both desistance from crime and recovery from substance use. Building on existing work attempting to measure and shift social networks and transitions to prosocial groups, the current study provides pilot data from prisoners and family members about a visualisation technique widely used in specialist addiction treatment (node-link mapping) to map opportunities for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…This is largely because of the increased significance of the sponsoring relationship and the intimacy and commitment to action which underpinned this type relationship. In this context, helping others, being productive and taking responsibility are meaningful practices but they are also key signifiers [ 32 ] in the self-categorisation process, as the self-help user transition into a new “non-addict” identity [ 12 , 13 ]. Over the longer term, sponsorship enables sponsors to practice a form of conventional living whilst still being part of a self-help group and maybe beneficial for those with limited access to conventional social worlds, groups and relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is largely because of the increased significance of the sponsoring relationship and the intimacy and commitment to action which underpinned this type relationship. In this context, helping others, being productive and taking responsibility are meaningful practices but they are also key signifiers [ 32 ] in the self-categorisation process, as the self-help user transition into a new “non-addict” identity [ 12 , 13 ]. Over the longer term, sponsorship enables sponsors to practice a form of conventional living whilst still being part of a self-help group and maybe beneficial for those with limited access to conventional social worlds, groups and relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Over the longer term, sponsorship enables sponsors to practice a form of conventional living whilst still being part of a self-help group and maybe beneficial for those with limited access to conventional social worlds, groups and relationships. Sponsorship provides the sponsor with social opportunities to enhance and maintain the new and more salient “in recovery” identity they are developing from their involvement [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is increasingly seen to be important by Government (see the Scottish Government, 2018, for an example of how this is being implemented in practice). The importance of connection is increasingly being highlighted in literature relating to recovery and desistance (McNeill et al, 2012; see also Best et al, 2018, for a further overview relating to social identity and community capital).…”
Section: Why the Lack Of Attention On The Needs Of Older Probation CLmentioning
confidence: 99%
“…Given the multiple barriers and complexity people in recovery from addiction experience, it is unsurprising that research indicates effective treatment is found when interventions are bespoke and solutions are tailored to meet the needs of individuals rather than adopting a "onesize fits all" approach (Peacock et al 2018). Indeed, recovery capital is integral to recovery and is nurtured through the delicate interplay of exposure and access to opportunities that help build a person's personal, psychological, social, and cultural strengths (Best et al 2018). Yet, exposure and access to opportunity alone are insufficient; instead, environments that are peerled, supportive, and offer pro-social networks and interactions (Bathish et al 2017) are critical.…”
mentioning
confidence: 99%